Parallel activation of de novo lipogenesis and stearoyl-CoA desaturase activity after 3 d of high-carbohydrate feeding. - Chong, M; Hodson, L; Bickerton, A; Roberts, R; Neville, M; Karpe, F; Frayn, K; Fielding, B (2008)
BACKGROUND: High-carbohydrate (HC) diets increase de novo lipogenesis (DNL), but effects on stearoyl-CoA desaturase (SCD) are not so well studied. OBJECTIVE: The objective was to investigate DNL and SCD in liver and adipose tissue by using fatty acid ratios after short-term dietary intervention. DESIGN: Eight subjects consumed isoenergetic 3-d HC (10% fat; 75% carbohydrates) or higher fat (HF; 40% fat; 45% carbohydrates) diets (sugar to starch ratio: 60:40 for both) in a crossover study. Blood was taken from an artery and a vein draining subcutaneous adipose tissue. DNL and SCD activity were investigated by using the ratios of 16:0 to 18:2n-6 and of 16:1n-7 to 16:0, respectively. A test meal, including [U-(13)C]palmitate was given to trace dietary fatty acid incorporation into VLDL-triacylglycerol (TG). The conversion of intravenously infused [(2)H(2)]palmitic acid to [(2)H(2)]palmitoleic acid in VLDL-TG was quantified as a specific marker of hepatic SCD activity. RESULTS: The VLDL-TG 16:0/18:2n-6 ratio, which reflects hepatic DNL, was greater after the HC diet than after the HF diet (P = 0.02). With the HC diet, increased plasma TG concentrations correlated with 16:0/18:2n-6 ratios (r = 0.76, P = 0.028). Plasma VLDL-TG and adipose venous nonesterified fatty acid (NEFA) 16:1n-7/16:0 ratios were higher after the HC diet (fasting: P = 0.01 and P = 0.05, respectively; postprandial: P = 0.03 and P = 0.05, respectively). Changes in fasting VLDL-TG 16:0/18:2n-6 and 16:1n-7/16:0 ratios were associated (P = 0.06). The contribution of total fatty acids from splanchnic sources (including DNL) was higher after the HC diet (P = 0.02). Expression of lipogenic genes in subcutaneous adipose tissue was not significantly affected by diet. CONCLUSION: Parallel activation of DNL and SCD was found after a short period of HC feeding.